Creating Logical Flow When Writing Scientific Articles - Barroga, Edward; Matanguihan, Glafera Janet (Journal of Korean Medical Science, 2021)
Numerous guidelines on how to write a scientific article have been published. Many books and articles giving detailed instructions on how to develop a research question, perform a literature search, or design a study protocol are widely available. However, there are few guidelines on how to create logical flow when writing a scientific article. Logical flow is the key to achieving a smooth and orderly progression of ideas, sentences, paragraphs, and content towards a convincing conclusion. This article provides guidelines for creating logical flow when writing the text and main sections of a scientific article. The first step is creating a draft outline of the whole article. Once completed, the draft outline is developed into a single, coherent article that logically explains the study. Logical flow in the text is created by using precise and concise words, composing clear sentences, and connecting well-structured paragraphs. The use of transitions connects sentences and paragraphs, ensuring clarity and coherence when presenting academic arguments and conclusions. Logical flow in the main sections of a scientific article is achieved by presenting the whole story of the article sequentially in the introduction, methods, results, and discussion, focusing attention on the most important points in each section, and connecting all of these to the main purpose of the study.